Reverse micro EDMed 3D hemispherical protruded micro feature: microstructural and mechanical characterization. (7th December 2018) - Roy, T; Datta, D; Balasubramaniam, R
Abstract: 3D hemispherical protruded micro features find wide application in various fields of surface engineering viz. micro lens let arrays, solar cells, energy conversion devices, heat transfer applications, tribological applications and many more. The present authors have already devised a technique for generating 3D hemispherical protruded micro feature by suitable tool modification in reverse micro EDM. In this paper, the microstructural and mechanical characterization of the already generated 3D hemispherical protruded micro feature is studied in order to determine the extent of the formed recast layer, heat affected zone (HAZ) and their mechanical properties viz. hardness, elastic modulus and residual stress in comparison to the parent material. Results indicate that the recast layer has higher hardness and elastic modulus followed by the hardened layer of HAZ as compared to the parent material. The soft layer of HAZ has the least hardness and elastic modulus. Qualitative analysis of residual stress using the loading and unloading portion of the load-displacement curves indicate that the recast layer has compressive residual stresses while the soft layer of HAZ has tensile residual stresses.